An 18-month clinical evaluation of prolonged polymerization of a universal adhesive in non-carious cervical lesions: A double-blind randomized clinical trial. Issue 1 (January 2022) - Hass, Viviane; Matos, Thalita P.; Parreiras, Sibelli O.; Szesz, Anna Luiza; de Souza, Jullian J.; Gutiérrez, Mario F.; Reis, Alessandra; Loguercio, Alessandro D.
Abstract: Objective: This study aimed to evaluate the effect of prolonging polymerization time on the 18 months clinical performance of a universal adhesive system used as etch-and-rinse (ER) and self-etch (SE). Methods: 140 restorations were randomly placed in 35 subjects according to the following groups: ER 10 (light-curing for 10 s); ER 40 (light-curing for 40 s); SE 10 (light-curing for 10 s) and; SE 40 (light-curing for 40 s/1200 mW/cm 2 ). A resin composite was placed incrementally. The restorations were evaluated at baseline and after 18 months by using the FDI criteria. The following outcomes were evaluated: marginal staining, marginal adaptation, spontaneous post-operative sensitivity and recurrence of caries. The differences among the groups were calculated using Friedman repeated measures analysis of variance rank (α = 0.05). Results: After 18 months the retention/fracture rates were 88.9% (95%CI 74.1–95.6%) for ER 10, 94.3% (95%CI 91.4–98.5%) for ER 40, 77.2% (95%CI 60.1–87.9) for SE 10 and 97.2% (95%CI 85.5–99.9%) for SE 40 . A significant difference was detected in the retention rate when SE 10 was compared to the SE40 (p = 0.01). Also, ER 40 showed a significant improvement of the marginal adaptation when compared to ER 10 (p = 0.01). Significance: This is the first study that demonstrates an improvement in the clinical performance of universal adhesive systems in non-carious cervical lesions when prolonged light-cured was applied.